Caracterização da formação de professores que trabalham com orientação sexual no ensino fundamental - Silva, Vera Lúcia Miranda da (2009)
This research had as objective to characterize the academic formation of the teachers of the 4th year of Elementary School that work with sexual orientation. To get it was developed explorative study focusing whit quali-quantitative evaluation, with 33 teachers who had answered to a questionnaire whit 33 questions about academic and professional formation, generalities characteristic of the professional performance, characteristic of the practical formation and conceptual aspects. The data collected had been analyzed by means of descriptive statistics and the open questions it was used of thematic analysis. The gotten results show that: 1) all the teachers from the studied schools are from female sex, age between 36 and 40 years old; 2) 76.0% the sexual them was not brought up in any subject; 3) teachers feel yourself unsatisfied with to the theoretical content and pedagogical strategy about sexual orientation at the College; 4) 87.9% said not to be prepared to act as orienting sexual; 5) 78.8% affirm that they had not subjects and contents about sexuality in theirs formation; 6) 90.9% reaffirm don´t had formation specify to work as orienting sexual; 7) the teachers said to have difficulty for working the subject and aren´t felling security and apt; and 8) the teachers are limited on didactic books of the school only in a boarding of biological contents. . As a result of this it’s advisable the inclusion of courses that may enlarge sexual studies and its bio-psycho-social difference.